Implementation Of The Kurikulum Merdeka At The Senior High School - Nadrah, Nadrah (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
The teachers who will carry out an kurikulum merdeka in their respective schools certainly prepare the learning process starting from the design of learning tools, implementation to learning evaluation. In the design process, teachers are still hesitant because they have to make considerable changes outside the norm and must adjust to the characteristics of the school and students, besides that there are quite crucial obstacles such as the ability of teachers to master IT where the kurikulum merdeka is full of IT, and there are also obstacles related to the understanding of the kurikulum merdeka, it is found that teachers do not really understand the independent curriculum itself, more precisely in the development of an kurikulum merdeka such as teachers are only equipped with learning outcomes and for the elaboration of the Learning Objectives Flow (ATP), Teaching Module (MA), Pancasila Student Profile, Learning Objectives Achievement Criteria (KKTP), Teaching at the Right Level (TaRL), Operational Curriculum in the Education Unit (KOSP) teachers are required to be able to develop until learning is carried out. The purpose of this study is to identify and obtain information about teacher readiness in designing learning tools. The method used in this study is a descriptive method, namely by describing the subject about the situation and the data obtained during the observation and interview so that it becomes information to overcome the problems found. The results of this study show that teachers experience obstacles in preparing for the implementation of an kurikulum merdeka. Teachers have tried to prepare learning both intracurricular learning and projects to strengthen the profile of pancasila students. However, teachers feel that the results of the learning design they have developed are not yet mature to be implemented in the classroom.